Design of a pre-water filter to provide aeration in filtration process - Lim, Jing jin (2014)
Occasionally, the tap water of housing area at Gambang, Pahang is detected to have the presence of odour and brownish in colour. The water filter cartridge turns brown rapidly. This issue has harassed the residents and caused doubtfulness by using the water supply. In order to verify this perception, tests of colour, turbidity, Biochemical Oxygen Demand (BOD), total solids (TS), total suspended solids (TSS) and total dissolved solids (TDS) were carried out by using the water supply from five houses in Gambang area. The results obtained were compared with the water quality standards. A pre-water filter was designed to solve this problem, which included an aeration and filtration process. The aeration process was induced by a free-fall in the system. Hence, the relationship between the height of the fall and dissolved oxygen level was determined to obtain the best and most feasible height in the aeration process. A high rate dual media filter with filter media of graded sand and activated carbon made from coconut shells;• and a support layer of gravel was used for the filtration process. By the completion of pre-water filter design, a running of the water filter was carried out and water after passed through the filter was then tested with colour, turbidity, BOD, TS and TSS amount, along with the confirmation of increased in dissolved oxygen value to ensure the water freshness. The results obtained were compared with the results of water before induced to the pre-water filter, and also the water quality standard. From this research, the final model of the pre-water filter was able to decrease above 50 % of the colour, turbidity, BOD, TS and TDS; and increased the dissolved oxygen level for 5.3 1%.